Prolonged ocular exposure leads to retinal lesions in mice. (August 2019) - Bell, Brent A.; Bonilha, Vera L.; Hagstrom, Stephanie A.; Anand-Apte, Bela; Hollyfield, Joe G.; Samuels, Ivy S.
Abstract: Retinal lesions in the posterior pole of laboratory mice occur due to native, developmental abnormalities or as a consequence of environmental or experimental conditions. In this study, we investigated the rate and extent of retinal lesions as a result of prolonged ocular exposure following general anesthesia. Following experimental preparation induction procedures (EPIP) involving general anesthesia, mydriasis/cycloplegia, and topical anesthesia to the cornea, two ocular recovery conditions (protected and unprotected) were tested within two different animal recovery chambers (open or closed). The anterior and posterior poles were evaluated for the development of retinal lesions using digital color photography, scanning laser ophthalmoscopy, and spectral-domain optical coherence during anesthesia recovery and up to 2.5 months thereafter. In some mice, electroretinograms, histological and immunohistological evaluations were performed to assess functional and structural changes that accompanied the retinal lesions detected by in vivo imaging. Our data suggests that prolonged ocular surface exposure to circulating ambient room air leads to significant anterior and posterior segment ocular complications. The most abundant, semi-reversible complication observed was the development of lesions in the outer retina, which had a 90% probability of occurring after 45 min of exposure. The lesions mostly resolved short-term, but functional and imaging evidence suggest that some perturbations to the outer retina may persist one or more months following initial development. Highlights: Experiments investigated the influence of post-procedural care on the development of ocular lesions in mice. Lenticular adhesions and outer retinal lesions occurred as a result of prolonged exposure to circulating ambient room air. Post-procedure ocular protection substantially reduced the risk of these undesirable complications.